Changes of Serum Total and Free Testosterone Concentrations in Male Chronic Hemodialysis Patients with Secondary Hyperparathyroidism in Response to Cinacalcet Treatment - Piotr Kuczera; Marcin Adamczak; Andrzej Wiecek (Karger Publishers, 2016)
Background/Aims: Calcium sensing receptor (CaSR) is expressed, among others also in testis. Cinacalcet binds to the CaSR, increases sensitivity of CaSR to serum calcium and is used in the treatment of secondary hyperparathyroidism (sHPT) in chronic hemodialysis patients (HDP). In most of male HDP, serum testosterone concentration is lower than in healthy males. The aim of this study was to assess the influence of six-month treatment with cinacalcet on the serum total and free testosterone concentration in male HDP with sHPT. Methods: 38 male, hemodialysed CKD patients with sHPT (PTH>300 pg/ml) were enrolled into the study. In each patient serum PTH, total testosterone (TT) and free testosterone (FT) concentrations were assessed before the first dose of cinacalcet and then after 3 and 6 months of treatment. The results are presented as means with 95% confidence interval. Results: In 33 patients who completed the study cinacalcet treatment caused significant decrease of serum PTH from 1143 pg/ml (828 - 1458 pg/ml) at the baseline, to 809 pg/ml (487 - 1132pg/ml) after 3 month of treatment (p = 0.002), and to 607 pg/ml (281 - 934pg/ml; p Conclusion: Treatment with cinacalcet decreases serum total and free testosterone concentration in male hemodialysed patients with chronic kidney disease and secondary hyperparathyroidism.